Poverty and Parenthood across Modern Nations: Findings from the Luxembourg Income Study - Timothy M. Smeeding; Karen Christopher; Paula England; Sara S. McLanahan; Katherin Ross (Luxembourg Income Study (LIS), 1999)
All modern societies face the issue of how to best support its children when labor and capital markets fail to produce adequate levels of income for their parents. Public and private means of economic and social support are mixed in rich nations to provide for both a minimally adequate level of economic and social support for families with children, and an equal opportunity for economic and social success amongst all children in the society. If we accept these goals, we might then measure failure to achieve the first outcome (adequacy) by the child poverty rate, and progress toward the second goal (equal opportunity) by the narrowness of the spread in incomes between the rich and poor in any a society. However, not all nations equally achieve these goals. If we create such measures as this, previous research has established that the United States has both the highest child poverty rate (20 percent or more) and the widest economic distance from poor to rich children of any modern (OECD) society. Others have published repeatedly on the high economic and social costs of child poverty in the United States and its social consequences. In fact, this disturbing outcome has provoked us to begin a set of wider and more complete studies designed to isolate the factors which produce poor child outcomes in the United States in comparison to those found in other nations. This paper is the second in a series of three related papers which try to examine why we find this outcome. The general rubric under which we are operating is termed 'the cost of children.' The rest of this introductory section of the paper discusses this project, the findings of our first paper on differences in poverty amongst men and women, and subsequent papers to follow. The second part of the paper presents our thoughts on the piece of the puzzle which we address here: the economic situation of parents and the poverty cost of parenthood. Next we discuss our definitions, data and methods (section III), results (section IV) and finally a summary discussion and conclusions (section V).
Keywords: 330; Kinder; Armutsbekämpfung; Familienleistungsausgleich; Industrieländer